2013
DOI: 10.1186/1472-6947-13-18
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse reactions from contrast agents for computed tomography

Abstract: BackgroundSymptoms of an adverse reaction to contrast agents for computed tomography are diverse ranging, and sometimes serious. The goal of this study is to create a scoring rule to predict adverse reactions to contrast agents used in computed tomography.MethodsThis was a retrospective cohort study of all adult patients undergoing contrast enhanced CT scan for 7 years. The subjects were randomly divided into either a derivation or validation group. Baseline data and clinically relevant factors were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Several methods have been used to prevent hypersensitivity to LOCM [27][28][29]. A previous history of hypersensitivity to LOCM is a major risk factor for further hypersensitivity [30], and several preventive strategies have been used in at-risk patients. Accurate documentation of the contrast agent that induced the response and history of iodine allergy should be evaluated [31], because a previous history of hypersensitivity is the main risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been used to prevent hypersensitivity to LOCM [27][28][29]. A previous history of hypersensitivity to LOCM is a major risk factor for further hypersensitivity [30], and several preventive strategies have been used in at-risk patients. Accurate documentation of the contrast agent that induced the response and history of iodine allergy should be evaluated [31], because a previous history of hypersensitivity is the main risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several other risk factors for hypersensitivity to LOCM have been identified [23,30,41,42]. In addition to past history of hypersensitivity, the presence of allergic disease, female gender, and younger age are associated with an increased risk of HSRs.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al reported in their large-scale study that the prevalence of all adverse reactions to nonionic contrast media was 2% and that of severe reactions was 0.1% [65]. The vast majority of these reactions were mild, including rash/hives, itching, nausea with or without vomiting, cough, or lump in the throat, among others.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…A recent study found an incidence rate of 0.0005%-0.0008% for severe reactions for nonionic contrast media. 5 Fatal reactions to both groups of iodine-based contrast media are very rare (1:170,000), with no difference in mortality reported between the two groups. 3,10,11 Physiological factors may also influence the incidence of acute adverse reactions.…”
Section: Incidencementioning
confidence: 98%
“…4 These observations have recently been confirmed in a large study of over 36,000 patients undergoing contrast-enhanced computed tomography with different nonionic agents. 5 The study showed that six factors are predictors of acute adverse reactions: (1) a history of adverse reaction to contrast media; (2) a history of urticaria; (3) any drug allergy; (4) a contrast media concentration .70%; (5) patient age under 50 years; and (6) a total contrast media dose above 65 g.…”
Section: Risk Factorsmentioning
confidence: 99%